Post-artesunate delayed haemolysis ‒ report of four cases and review of the literature (Swiss Medical Weekly, 2015)
As a result of a huge effort of the international community, the burden of malaria dropped impressively during the last decade. One of the reasons is probably the availability of effective and safe treatments such as artemisinin derivatives. However, along with the greater use of intravenous artesunate recently in severe malaria, as recommended by the World Health Organization, a new adverse event has been described: post-artesunate delayed haemolysis (PADH). It appears after the end of the treatment in a phase of clinical improvement. Even though several causes may act as co-factors, the mechanism of pitting of the infected erythrocytes is most probably the main explanation. After the description of four PADH cases, we hereby present a short review of the current knowledge on this problem.